Application of organic soybean tempeh in purple sweet potato raisin cookie - Tangthirasunun, N.; Poeaim, S. (International Journal of Agricultural Technology, 2022)
Organic soybean tempeh or tempeh kedelai is made by fermentation with Rhizopus oligosporus was used to produce cookies, as a plant-based protein snack. Four samples with various recipes - purple sweet potato cookie, purple sweet potato raisin cookie, tempeh purple sweet potato cookie and tempeh purple sweet potato raisin cookie – were prepared to determine the physicochemical and sensory features. Chemical analysis found that the tempeh purple sweet potato raisin cookie has the highest moisture (18%) and total proteins (29%). However, the purple sweet potato cookies showed the highest ashes content (2%) and tempeh purple sweet potato cookie showed the highest total lipids (29%). The tempeh purple sweet potato raisin cookie was hardest (61 N). The tempeh purple sweet potato raisin cookie had the highest scores for food acceptability of all qualities in appearance, texture, aroma, colour, taste and general acceptability using a 9-point hedonic scale ranging from slightly liked to very much liked. Therefore, the tempeh purple sweet potato raisin cookie can be accepted as a new snack, that includes a good level of protein and thus a healthy food alternative. Furthermore, if all steps of the production are carefully controlled by USDA or other certifying bodies, thus this product may be labelled as organic product.